The Use of Homework as an Instructional Tool by Moroccan EFL Teacher - OUBIT, SIDI MOHAMED; EL FARAHI, Abdellatif (Technium Education and Humanities, 2025)
Far from discussing the controversial issues related to the relationship between homework and students’ academic achievement, the present article focuses on the way this instructional technique is implemented by Moroccan EFL teachers. To meet this goal, I try to dig into a major perspective: the teacher. In this article, EFL teachers working in Laayoune Sakia Elhamra region receive a varied survey to complete. The data from these surveys are categorized based upon sub- questions. In addition to questionnaires, as a tool of data collection, this study adopts two other tools: observations and teachers’ interviews. Upon completion of categorizing the data, an analysis and reflection of the data is performed summarizing and interpreting what the data represent. Given the fact that this article is a snapshot of the way homework is implemented in teaching English as an FL, it culminates in pedagogical implications and recommendations for teachers, students, parents, administrators, supervisors and future research.